2011
DOI: 10.5598/imafungus.2011.02.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Fleming’s penicillin producing strain is not Penicillium chrysogenum but P. rubens

Abstract: Penicillium chrysogenum is a commonly occurring mould in indoor environments and foods, and has gained much attention for its use in the production of the antibiotic penicillin. Phylogenetic analysis of the most important penicillin producing P. chrysogenum isolates revealed the presence of two highly supported clades, and we show here that these two clades represent two species, P. chrysogenum and P. rubens. These species are phenotypically similar, but extrolite analysis shows that P. chrysogenum produces se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(165 citation statements)
references
References 27 publications
5
153
1
6
Order By: Relevance
“…Curiously, to date, P. rubens has not shown any link to clinical isolates, although it is a recently resurrected species, closely related to P. chrysogenum (29). In contrast, P. chrysogenum has already been identified as a human pathogen associated with cutaneous and invasive infections (8,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, to date, P. rubens has not shown any link to clinical isolates, although it is a recently resurrected species, closely related to P. chrysogenum (29). In contrast, P. chrysogenum has already been identified as a human pathogen associated with cutaneous and invasive infections (8,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found different Penicillium taxa associated with the Antarctic macroalgae. According to Frisvad and Samson (2004), Scott et al (2004) and Houbraken et al (2011), the taxonomy of the group Penicillium has been regarded to be especially difficult and needs a polyphasic study including physiological, morphological, multilocus sequence typing and chemical methods. For these reasons, the Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…A number of compounds from this genus have been characterised and used for drugs and mycotoxins. For example, the antibiotic penicillin is produced by Penicillium rubens (Houbraken et al 2011), the immunosuppressive drug mycophenolic acid is produced by Penicillium brevicompactum (Regueira et al 2011). There were many new compounds that have been found constantly in the following years with impressive anticancer and antifungal activities (Bladt et al 2013; Kozlovskii et al 2013; Tang et al 2015; Koul et al 2016).…”
Section: Introductionmentioning
confidence: 99%